Design of Fir Digital Bandpass Filter with Hamming Window and Hanning Window Method for Fetal Doppler - Hartono Siswono; Widyastuti Widyastuti; Yohanes Dovan; Dyah Nur’ainingsih (Universitas Ahmad Dahlan, 2023)
Fetal heart rate using Doppler Ultrasound is a standard method to assess fetal health. Examination of the fetal heart with a Doppler device is more convenient for women. Fetal Doppler can accidentally take the mother's heartbeat. A filter is needed to enhance the audibility of fetal heartbeats while suppressing unwanted frequencies and noise. The normal fetal heart rate ranges from 120 to 160 beats per minute, or 2 Hz - 3 Hz. This frequency can be filtered using a bandpass filter. the digital FIR bandpass filter were created using the Hamming and Hanning window methods. The results of the FIR filter with the Hamming and Hanning window, Orde 100 Hanning gave the best frequency bandwidth range which was 1.833 Hz to 3.167 Hz. Orde 20 Hamming and Hanning had the shortest delay +- 2 s and Orde 100 Hamming and Hanning had the longest delay +- 6s. For the noise at 1.6 Hz, Orde 100 Hamming and Orde 100 Hanning the signal level of the signal output is the same as the desired signal level. For the noise at 3.1 Hz, Orde 100 Hamming and Orde 100 Hanning had the signal level of the signal output is almost the same as the desired signal level. At the frequency point of 1.6 Hz, the noise signal at the input has a magnitude response 2533, it is a decrease after passing through the filter to = 0. At the frequency point of 3.1 Hz, the noise signal at the input has a magnitude response 2246, and there is a decrease after passing through the filter to 167.7. From this study, we can choose 100 orde Hanning because it gave the best frequency bandwidth range which was 1.833 Hz to 3.167 Hz, the delay of +- 6s.